Pemanfaatan Limbah Plastik Menjadi Rak Sepatu Menggunakan Meterial Botol Plastik Aqua - Jaelani Jaelani; Sudarmono Sudarmono; Fika Rizki Oktariani (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
A collection of shoes that are not neatly arranged often makes you lazy to tidy up and clean them, whereas the condition of scattered shoes can spoil the view and reduce the durability and functionality of the shoes themselves. On the other hand, plastic waste, especially plastic bottles, is increasing and becoming a serious problem for the environment. In an effort to reduce the impact of pollution and utilize unused items, this study proposes a solution in the form of making a shoe rack from used plastic bottle waste. The use of plastic bottles not only reduces the amount of waste but also provides a practical solution for more organized shoe storage, especially for students who need efficient and environmentally friendly shoe storage space. The method used in this study is (R&D), which aims to develop a shoe rack product and test its effectiveness and feasibility. The test results show that this shoe rack can accommodate 12 pairs of shoes with a maximum strength of 5.5 kg per rack consisting of three levels. The use of 69 plastic bottles for the base and 24 bottles for the walls provides a large enough capacity to store shoes. Based on the test results, this shoe rack not only functions as a place to store shoes, but also as an effort to reduce plastic waste and support environmental sustainability. This product can also be used as an example in learning product design, recycling, and entrepreneurship.